Physicians' lifelong learning journeys: A narrative analysis of continuing professional development struggles - Louise Allen; Dorene F. Balmer; Lara Varpio (2024)
Despite tenacious efforts of continuing professional development (CPD) developers and educators, physician engagement in CPD is fraught with challenges. Research suggests that these educational interventions and the maintenance of professional competence systems that mandate them are often seen as impractical, decontextualized and check-box activities by participants. This study explores physicians' learning post graduate medical education (GME) training across their CPD journey to understand how they (a) conceive of themselves as learners and (b) engage in lifelong learning across the course of their professional careers.